(untitled) (Bangladesh Journal of Medical Science, 2022)
Choledocholithiasis is the presence of stones in the common bile duct (CBD). Choledocholithiasis in post-cholecystectomy is rare. Nonetheless, this is a report of a 40-year-old woman who was presented with severe epigastric pain with high-grade fever, tea-coloured urine, pale stool, and jaundice. She had a history of pangastritis and had cholecystectomy two years ago.This case report describes the significant diagnostic dilemma of the choledocholithiasis, particularly in a post-cholecystectomy patient who had pangastritis and was presented with severe epigastric pain. The diagnosis of choledocholithiasis was missed as the early symptoms of choledocholithiasis are similar to those of pangastritis. Therefore, treatment for choledocholithiasis was delayed. A high index of suspicion for diagnosis of choledocholithiasis must be emphasized among primary care practitioners even in a post-cholecystectomy patient. This will enable early treatment for the patient and prevent complications such as ascending cholangitis and sepsis. Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 458-462